How organizational support enhances polytechnic lecturers' performance: The mediating role of competence and the moderating role of motivation - Sri Porwani; Mohamad Adam; Zunaidah Zunadiah; Yuliani Yuliani; Ferry Jie (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2026)
Despite the critical role of polytechnic lecturers in vocational education, empirical evidence remains limited regarding how organizational support translates into improved lecturer performance through competence and motivation. This study addresses this gap by examining a moderated mediation model linking organizational support, lecturer competence, motivation, and performance. A quantitative correlational design was employed involving 185 lecturers from private polytechnics across various technical disciplines in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that organizational support significantly enhances lecturer competence (β = 0.45, p < 0.001), while competence strongly predicts lecturer performance (β = 0.50, p < 0.001). Competence fully mediates the relationship between organizational support and performance (β = 0.23, p < 0.01), whereas motivation significantly strengthens the competence–performance relationship (β = 0.22, p < 0.01), supporting the proposed moderated mediation model. These findings provide novel evidence that sustainable lecturer performance depends not only on organizational support but also on competence development and motivational conditions. The study contributes to organizational support theory within vocational higher education and offers practical guidance for designing competence-centered professional development and motivation-enhancing strategies to improve lecturer effectiveness.